UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PAKEM PADA MATA PELAJARAN MATEMATIKA DI KELAS I - Musiatun Musiatun (Dharmas Education Journal (DE_Journal), 2021)
The problem of this research is the low students’ scores of learning outcomes in themes 9 things around us, sub themes 1 single object and mix objects proved by accomplished their midterm test that over than minimum criteria of mastery, total 11 students and 15 students who do not through to the minimum criteria of mastery. The goal of this research is to fix the students’ low learning outcomes by using applying talking stick model. Kind of this research is classroom action research. The subjects of this research were all of students of class V that had 26 students, consisted of 9 boys and 17 girls. This research had four stages, they are planning, implementation, observation and reflection. In this research, researcher did 2 cycles. Each cycle had three meetings. Collecting the data using teacher observation sheet, student worksheet, student overcomes test, and documentation. The result of the research shows that the teacher’s activities at the first cycle that is categorized good, the second meeting is good categorized, and the third meeting is good. Students activities at the first cycle on the first meeting categorized is good enough, second meeting is good, the third meeting is good. At the second cycle on the first meeting is categorized good, the second meeting is good, the third meeting is good. Students’ problems in first cycle is reached to 58% and the second cycle is reached 85%. Referring to the result, it can be assumed that learning through talking stick model on learning themes 1 single object and mix objects can increase students’ learning outcomes.